Why cholecystokinin and gastrin are also incretins. Issue 3 (September 2016) - Rehfeld, Jens F.
Abstract : This review argues that cholecystokinin (CCK) and gastrin are incretins. The insulin cells are equipped with CCK2 /gastrin receptors. CCK/gastrin peptides stimulate insulin secretion and potentiate the incretin effect of glucagon-like peptide-1. CCK/gastrin and insulin are released in significant amounts during normal mixed meals even at modest changes in blood glucose concentrations. Treatment of diabetes patients with combinatorial glucagon-like peptide-1 and CCK or gastrin-derived constructs therefore provides an expedient option.